Analysis of Road Network Vulnerability for Dempo Volcano Eruption Evacuation - Aprilia, Gita; Hardiansyah, Hardiansyah; Mase, Lindung Zalbuin; Misliniyati, Rena; Amri, Khairul (Journal Innovation of Civil Engineering (JICE), 2025)
South Sumatra is a province on the island of Sumatra, positioned along the boundary between the Indo-Australian Plate and the Eurasian Plate. The tectonic interaction between these plates has resulted in a mountain range that extends longitudinally from the island’s northern to southern regions, a geological condition that contributes to the area’s susceptibility to natural hazards, one example is the Dempo Volcano. This study uses the four-step model method to analyse the vulnerability of the road network on evacuation routes during the eruption of Dempo Volcano in Pagar Alam City. Eight road sections were observed. A comparison of traffic survey results and numerical modelling was conducted to assess the consistency of the model and also to predict critical conditions. Scenario 1 represents evacuation conditions without any changes to road geometry, while Scenario 2 represents evacuation conditions with modifications in the form of road widening. The analysis showed that most of the population prefers motorcycles as a mode of transport and the fastest route during evacuation, considering the faster evacuation time. Scenario 1 showed a surge in traffic volume, which became an obstacle to evacuation. Scenario 2 can increase capacity and improve traffic flow. The Vulnerability Index indicates that some road sections are vulnerable to evacuation impacts. Keywords: Disaster Evacuation; Four Steps Models; Dempo Volcano Eruption; Road Network Modelling; Vulnerability Index.